CONTROLLING THE INTEREST RATE RISK OF A PROPERTY-LIABILITY INSURANCE FIRM - Gougeon, Patrick (Assurances)

(untitled) (HEC Montréal, 1998)
Deregulation and globalisation have contributed to increase the volatility of financial markets. As a result understanding and controlling the risk arising from changes in interest rates has become a major issue, particularly for financial intermediaries which are considered most exposed to it. In this paper the author addresses the particular case of a property-liability insurance firm. Once basic concepts have been presented, the determinants of the interest rate risk exposure are identified. A discussion follows to analyse the difficulties encountered to control the risk and to present possible risk reducing strategies. The author observes that the necessary conditions for immunisation might be difficult to fulfil, particularly when the goodwill represents a significant part of the firm's economic value of assets. The complexity of the situation and the importance of subjective factors in the determination of the interest rate risk exposure of the insurer's equity value are finally presented in the conclusion as major impediments to more rationality from investors which might well expIain a high volatility of insurance stock prices.